Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T14:31:09+01:00
A) x³ +ax²+3x+1-(2x²+bx-4)=x³-7x²+8x+5
x³ +ax²+3x+1-2x²-bx+4=x³-7x²+8x+5
x³ +ax²-2x²+3x-bx+5=x³-7x²+8x+5
x³+(a-2)x²+(3-b)x+5=x³-7x²+8x+5
teraz przyrownujemy odpowiedznie wyrazenia
(a-2)x²=-7x²
(a-2)=-7
a=-5
(3-b)x=8x
3-b=8
-b=5
b=-5

b)
2x³+ax²+5x-3-(x³-5x²+bx+4)=x³+2x²+4x-7
2x³+ax²+5x-3-x³+5x²-bx-4=x³+2x²+4x-7
x³+ax²+5x²+5x-bx-7=x³+2x²+4x-7
x³+(a+5)x²+(5-b)x-7=x³+2x²+4x-7

(a+5)x²=2x²
a+5=2
a=-3
5-b=4
-b=-1
b=1
3 3 3
2010-02-16T15:18:32+01:00
A) W(x)-F(x)=H(x)
Podstawiamy wielomiany:
x³+ax²+3x+1-(2x²+bx-4)=x³-7x²+8x+5
x³+ax²+3x+1-2x²-bx+4=x³-7x²+8x+5
x³+(a-2)x²+(3-b)x+4=x³-7x²+8x+5
Porównujemy odpowiednie współczynniki, otrzymując układ równań:
a-2=-7
3-b=8

a=-5
b=-5

b) 2x³+ax²+5x-3-(x³-5x²+bx+4)=x³+2x²+4x-7
2x³+ax²+5x-3-x³+5x²-bx-4=x³+2x²+4x-7
x³+(a+5)x²+(5-b)x-7=x³+2x²+4x-7

a+5=2
5-b=4

a=-3
b=1
3 3 3